From the periphery to peripheries? For the creation of a new theoretical framework for studying suburban areas in Brazil - Cerqueira, Eugênia Dória Viana (2022)
In recent decades, there has been an evolution of peripheral areas, guided by a process of socio-spatial complexification and diversification. Thus, this paper advocates for the development of a renewed theoretical framework in urban literature, beyond the traditional twofold approach that focuses on the antagonism between central and peripheral areas. A critical bibliographic review is carried out, supported by illustrative examples collected during fieldwork carried out in the Metropolitan Region of Belo Horizonte.